Understanding the Objectives and Functions of Language Development in Early Children - Imam Tabroni; Aghny Himatun Mujahideen; Unang Wahidin; Wahyudin Wahyudin (Institute of Computer Science (IOCS), 2022)
Children acquire hazard abilities in many ways. Language is the most important form because language can shape our perception, communication and daily interaction. Language is a system that categorizes, organizes, and classifies our thoughts. Aspects of language development listed in the national PAUD standards consist of: understanding receptive language, expressing language and literacy. In this aspect of language development, all aspects of a child's language must be stimulated properly, because the development of a child's language is very important to support the next life. To develop children's language intelligence or commonly called children's language development, there are many factors that need to be considered, especially in terms of children's health factors, intelligence, social factors, and family relationships.